Properties of ubiquitous modes in tokamak plasmas. (21st August 2019) - Shen, Yong; Dong, J.Q.; Li, J.; Han, M.K.; Li, J.Q.; Sun, A.P.; Qu, H.P.
Abstract: The comprehensive study of ubiquitous modes (UMs) was performed by means of gyrokinetic simulation, employing the gyrokinetic equations for drift waves in the frequency regime of in tokamak plasmas. The results show that the UMs are mostly in the short wave length regime of, with being the average ion gyroradius, and the ion gyrofrequency. It was demonstrated that a fluid-like instability may occur when, and . The results suggest that both trapped electrons and electron/ion density gradient are involved in the driving of UMs. The ion temperature gradient has a significant impact on UM instability. A lower electron temperature gradient, higher ion temperature gradient, adequate fraction of trapped electrons, and limited magnetic shear ( is optimum) are required for UMs to be unstable. The mode structure is highly localized. It was also indicated that the UMs are usually inevitable in tokamak plasmas and may contribute greatly to plasma transport in specific parameter regimes.